2017
DOI: 10.1111/dom.12989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined low‐dose spironolactone plus vitamin E vs vitamin E monotherapy on insulin resistance, non‐invasive indices of steatosis and fibrosis, and adipokine levels in non‐alcoholic fatty liver disease: a randomized controlled trial

Abstract: The beneficial effects of mineralocorticoid receptor blockade by spironolactone have been shown in animal models of non-alcoholic fatty liver disease (NAFLD). The aim of the present 52-week randomized controlled trial was to compare the effects of low-dose spironolactone and vitamin E combination with those of vitamin E monotherapy on insulin resistance, non-invasive indices of hepatic steatosis and fibrosis, liver function tests, circulating adipokines and hormones in patients with histologically confirmed NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 19 publications
(18 reference statements)
1
36
1
1
Order By: Relevance
“…The study by Aller et al did not clearly define the randomization strategy and included a combination therapy of vitamin E and silymarin tested against lifestyle modifications [16]. One double-blinded RCT compared a combination therapy of atorvastatin, vitamin C, and vitamin E and placebo [14]; the other double-blinded study compared vitamin E monotherapy and vitamin E combination therapy with spironolactone [17], and another compared δ-tocotrienol monotherapy therapy and placebo [18]. Three studies were triple-arm double-blinded RCTs where at least one group was given vitamin E as a monotherapy [13,15,19].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Aller et al did not clearly define the randomization strategy and included a combination therapy of vitamin E and silymarin tested against lifestyle modifications [16]. One double-blinded RCT compared a combination therapy of atorvastatin, vitamin C, and vitamin E and placebo [14]; the other double-blinded study compared vitamin E monotherapy and vitamin E combination therapy with spironolactone [17], and another compared δ-tocotrienol monotherapy therapy and placebo [18]. Three studies were triple-arm double-blinded RCTs where at least one group was given vitamin E as a monotherapy [13,15,19].…”
Section: Resultsmentioning
confidence: 99%
“…An interventional study which demonstrated the beneficial effect of combined low dose of spironolactone plus vitamin E in patients with NAFLD did not report a significant decrease of leptin levels in the group which received the regimen [ 53 ]. Similarly, another study with rosiglitazone treatment in patients with NAFLD showed that the significant improvement in liver function was not accompanied by significant changes in plasma leptin levels [ 54 ].…”
Section: Leptinmentioning
confidence: 99%
“…Yao et al demonstrated that silymarin ameliorated insulin resistance in NASH rats and proposed that this natural compound was able to modulate the expression of genes involved in visceral obesity, lipolysis and gluconeogenesis [48]. The same role was not delineated for vitamin E since the biomolecule alone seemed not able to repair damaged insulin response mechanisms [49]. Some mechanisms through which DHA exerts this property emerged from studies on animals: anti-inflammatory effects and modulation of the expression of related gene were proposed [50]; similarly, curbed insulin resistance was obtained by supplementation with only CGA in animals with HFD-induced hepatic steatosis [51].…”
Section: Discussionmentioning
confidence: 99%